KAJIAN MANAJEMEN PERUBAHAN DALAM IMPLEMENTASI REFORMASI BIROKRASI DI PEMERINTAH KABUPATEN KUTAI KARTANEGARA - sabran sabran; Toni Nurhadi Kumayza (MAHAKAM: Jurnal Ilmu-Ilmu Sosial, 2015)
Administrative reform is not a reform in the political system, campaign finance reform or reform of the legislature but rather to update the restructuring of the organization and the system of government by changing objectives, work culture, mindset and working mechanism. governments need increasingly brought closer to the people so that they can respond quickly to the needs of a dynamic society. governance is within reach of the public, the service provided to be faster, responsive, accommodating, innovative, productive, and economicalExpected better public bureaucracy in providing public services and become more professional in their duties and authority. In order to achieve a good public service does a lot of things that need to be repaired and one reform the bureaucracyKey word: Administrative reform